Drag reduction in Newtonian polymer solutions - Hershey, Harry C. (1965)
"Prior work in the area of drag reduction has been mainly limited to aqueous solutions. Theoretical and empirical analyses of the resulting data in aqueous solutions have been hindered by the fact that some polymers cause drag reduction and others do not...This investigation was directed to the study of how the size and configuration of the polymer molecule in solution affected drag reduction and the related phenomenon of turbulence suppression. Apparatuses were designed and built to measure viscometric flow, curves, friction factors, velocity profiles, and normal stresses (by a jet thrust technique developed by Metzner and associates)"--Summary, leaves 1-2.